Risk Perception and Condom-use among Thai Youths: Findings from Kanchanaburi Demographic Surveillance System Site in Thailand (Journal of Health, Population and Nutrition, 2010)
Youths, aged 15-24 years, comprise a large fragment of the total population in Thailand, and unsafe sexual behaviours are increasing, nowadays, among young people. The study was conducted to explore the characteristics of youths and other conducive, facilitating and reinforcing factors associated with risk perception of sexually transmitted infections (STIs) among the study population. Data employed in this study were derived from the site of the Kanchanaburi Demographic Surveillance System of Thailand 2004 using a stratified systemic design. The study population was mainly young current condom-users aged 15-24 years, and cross-sectional analysis was done on this populace. The findings revealed that youths who fell into the single (unmarried) category having temporary partners were more likely to perceive the risks associated with STIs in relation to using condom. A greater proportion of unmarried youths was engaged in sexual activity before the age of 20 years and that condom-use was also inconsistent. Youths having temporary partners were more likely to perceive risk and reason for using a condom than when with their regular partner. Education played a significant role in risk perception of STIs. Risk perception was increasing with the increasing level of education. Other conducive and facilitating factors, such as household wealth, living in urban or semi-urban areas, and access to mass media such as television, also had a positive influence on risk perception. The odds ratio showed that condom-users who had indulgence in liquor were less likely to perceive the risk of STIs. Overall, socioeconomic status had a great influence on risk perception of STIs. Finally, youths exhibiting high-risk sexual behaviour need realistic risk assessments and positive ways of incorporating condom into their sexual lives. Key words: Condom-use; Education; Risk perception; Sexual partners; Youths; Thailand DOI: 10.3329/jhpn.v27i6.4329 J Health Popul Nutr 2009 Dec; 27(6): 772-783